An Assessment of School Management Disciplinary Practices and its Influence on Students’ Unrest Management in Public Secondary School in Meru County of Kenya - Jacob, Bundi Marete; Mugwe, Mary; Reche, George N.; Ochieng, Pamela (International Journal For Research In Educational Studies, 2020)
This study focused on assessment of the schools disciplinary practices and its influence on students’ unrest management in public secondary school in Meru county of Kenya. In Meru County, the rate of students’ unrest is about 30 % while the national average is about 10% of all cases reported in year 2017. This rate is way above the national average. The objectives of the study were; To determine method of selecting student councils, and its influence of student unrests in public schools in Meru county of Kenya, to establish whether students councils are trained, and its influence on students unrest management in public secondary schools in Meru county of Kenya, to establish whether schools have defined disciplinary procedure, and its influence on schools unrest in Meru county of Kenya and to investigate whether schools have suggestion boxes, and its influence on student unrest in schools in Meru Kenya. The study used mixed method of research. The conclusion of the study was schools student councils are constituted in all schools. Most student councils met regularly and parents were consulted on matters affecting students, on membership of the council the findings indicated that the principal and the staff members guided students on appointing the council / selecting them. Also the student councils handled a lot of responsibilities in punishing student’s resulting in conflicts and students unrest.